The evolution of Maghreb nationalist movements through Swiss diplomatic correspondence (1945-1958) via DODIS- diplomatic documents of Switzerland. - MERDJAA , Aicha (La Revue d’Histoire Méditerranéenne, 2024)
This research paper examines the Swiss diplomatic archives as a crucial foreign source for studying the history of Maghreb nationalist movements. Alongside reports and diplomatic correspondence, it also incorporates other available sources and previous studies to trace the evolution of nationalist liberation movements in Tunisia, Morocco, and Algeria. The study explores colonial policies and strategies designed to suppress these movements, aiming to reveal how Swiss diplomatic correspondences described and interpreted their trajectory. By systematically analyzing reports and correspondence from Swiss diplomatic missions available on the DODIS platform, the study follows the chronological development of these movements, focusing on pivotal historical events that influenced Switzerland’s fluctuating stance- sometimes supportive, sometimes oppositional-toward the Maghreb’s independence efforts. This study seeks to uncover the reasons behind these shifts in Swiss policy, offering a foundation for further inquiries into Swiss-Maghreb relations during the colonial period. In doing so, the study also highlights the valuable potential of Switzerland’s digital diplomatic archives as a resource for future research.